Arm morbidity of axillary dissection with sentinel node biopsy versus delayed axillary dissection. Issue 9 (2nd February 2018) - Ballal, Helen; Hunt, Catherine; Bharat, Chrianna; Murray, Kevin; Kamyab, Roshi; Saunders, Christobel
Abstract : Background: Staging of axillary lymph nodes in breast cancer is important for prognostication and planning of adjuvant therapy. The traditional practice of proceeding to axillary lymph node dissection (ALND) if sentinel lymph node biopsy (SLNB) is positive is being challenged and clinical trials are underway. For many centres, this will mean a move away from intra‐operative SLNB assessment and utilization of a second procedure to perform ALND. It is sometimes perceived that a delayed ALND results in increased tissue damage and thus increased morbidity. We compared morbidity in those undergoing SLNB only, or ALND as a one‐ or two‐stage procedure. Methods: A retrospective review of a prospectively collected institutional database was used to review rates of lymphoedema and shoulder function in women undergoing breast cancer surgery between 2008 and 2012. Results: The overall lymphoedema rate in 745 patients was 8.2% at 12 months. There was no difference in lymphoedema rates between those undergoing immediate or delayed ALND (17.8 and 8.6%, respectively, P = 0.092). Post‐operative shoulder elevation, odds ratio (OR) = 0.390, 95% confidence interval (CI) = (0.218, 0.698) and abduction, OR = 0.437 (95% CI = (0.271, 0.705)) were reduced if an ALND was performed although there was no difference between immediate or delayed. Conclusion: ALND remains a risk factor for post‐operative morbidity. There is no increased risk of lymphoedema or shoulder function deficit with a positive SLNB and delayed ALND compared to immediate ALND.